Produção de quitosana e bioemulsificante por Rhizopus microsporus (UCP 1304) através da fermentação submersa utilizando resíduos agroindustriais. - Araújo, Josué Félix de (2018)
The use of alternatives substrates previously discarded in the environment has been interesting for being reused in the formulation of means of production in biotechnological materials such as chitosan and bioemulsifiers. In this work was investigated the simultaneous production of chitosan and bioemulsifier, from the cultivation of Rhizopus microsporus UCP 1304, in a medium containing malt bagasse, molasses and tomato broth as agroindustrial waste, through submerged fermentation. Chitosan-based biomaterials constitute an emerging class with application in various fields opened to exploration by micro-organisms such as yeasts and fungi. Fungal chitosan has less toxicity and better compatibility compared to crustacean’s chitosan. The bioemulsifier obtained from a medium formulated by alternative substrates represents greater economics and better sustainability, besides constitute a viable alternative and a new world tendency for scientific research and arouses the industrial interest. The results showed that Rhizopus microsporus, was able to biotransform agroindustrial wastes, demonstrating an important yield in biomass, chitin, biomass chitosan and bioemulsifier production from alternatives substrates.